Rancang Bangun Alat Pengecat Dinding Semi Otomatis Berbasis Mikrokotrolel ATMega8535 - Jupri Yanda Zaira (Jurnal Elektro dan Mesin Terapan, 2020)
The painting process is a necessity to beautify a room, where automatic wall painting tools can be used as a solution to lighten human work that can help routine tasks in the process of painting walls in a room. The system used in the design of the automatic wall painting tool is to use the ATMega8535 microcontroller control system. The test is carried out by making the initial settings on the painting tool that has been determined, after which the controller button is activated, and then the tool will immediately paint the wall semi automatically, where the movement of the tool arm uses a DC motor power window, and the paint brush uses a rolers that is usually used to paint wall in a room. The movement of the design and construction of this wall painting tool is carried out automatically, where the command from the push button will be processed in the microcontroller, namely ATMega8535 before being forwarded to the actuator, namely the DC motor which is regulated by the motor driver. The results of this study are this wall painting tool has a painting range of 2 m x 2 m with a time of 27.3 minutes, and to get an even result, it must be done 3 times. The maximum motor capacity required to operate the wall painters for the power window motor is a maximum of 18.13 VA, and for a DC motor the maximum is 18.32 VA.